2016
DOI: 10.1111/gcb.13450
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition nitrogen is better retained than simulated deposition from mineral amendments in a temperate forest

Abstract: Nitrogen (N) deposition (N DEP ) drives forest carbon (C) sequestration but the size of this effect is still uncertain. In the field, an estimate of these effects can be obtained by applying mineral N fertilizers over the soil or forest canopy. A 15 N label in the fertilizer can be then used to trace the movement of the added N into ecosystem pools and deduce a C effect. However, N recycling via litter decomposition provides most of the nutrition for trees, even under heavy N DEP inputs. If this recycled litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 92 publications
(108 reference statements)
1
0
0
Order By: Relevance
“…In our N-saturated system, litter manipulation had an immediate effect on soil N pool, such as direct positive effects on (NH 4 -N) and (NO 3 -N) concentration ( Table 2, Figures 3 and 6). Similar to previous studies, the results suggested that litter decomposition increased the (NH 4 -N) pool [55], being retained in the soil litter layer, partitioned differently than mineral N fertilizer 'deposition' [56,57]. Furthermore, (NO 3 -N) of CK and LA in N3 plots showed the significantly higher mean values than other treatments (Figure 3b), which suggests that litter, to some extent, could mitigate the (NO 3 -N) leaching [58].…”
Section: Impacts Of Litter Manipulation On N-saturated Soilsupporting
confidence: 88%
“…In our N-saturated system, litter manipulation had an immediate effect on soil N pool, such as direct positive effects on (NH 4 -N) and (NO 3 -N) concentration ( Table 2, Figures 3 and 6). Similar to previous studies, the results suggested that litter decomposition increased the (NH 4 -N) pool [55], being retained in the soil litter layer, partitioned differently than mineral N fertilizer 'deposition' [56,57]. Furthermore, (NO 3 -N) of CK and LA in N3 plots showed the significantly higher mean values than other treatments (Figure 3b), which suggests that litter, to some extent, could mitigate the (NO 3 -N) leaching [58].…”
Section: Impacts Of Litter Manipulation On N-saturated Soilsupporting
confidence: 88%